Estimating immigrant citizenship rates in Canada and the United States: Data sources and comparability issues - Feng Hou; Garnett Picot; Li Xu (Economic and Social Reports)
The United States would be a useful comparison country for Canada in studying immigrant naturalization, as both are major immigrant-receiving nations with close geographic and economic ties. However, differences in available data complicate comparisons of immigrant citizenship rates. This article examines key data sources for studying immigrant citizenship in both countries and highlights the challenges in comparing citizenship rates and trends.